Pola makan, asupan zat gizi, dan status gizi anak balita Suku Anak Dalam di Nyogan Kabupaten Muaro Jambi Provinsi Jambi - Erni Erni; Muhammad Jufrrie; Muhammad Primiaji Rialihanto (Jurnal Gizi Klinik Indonesia, 2008)
Background: Anak Dalam Tribal Community lives in an isolated area with meagre living pattern and numerous limitations. This condition affects eating pattern and nutritional status of underfives of Anak Dalam Tribe.Objective: To identify eating pattern, nutrient intake, and nutritional status of underfives of Anak Dalam Tribe at Nyogan, District of Muaro Jambi, Province of Jambi.Method: The study was observational with cross sectional design. Population of the study were underfives of Anak Dalam Tribe aged 24–59 months at Nyogan, District of Muaro Jambi, Province of Jambi. Data obtained consisted of eating pattern, nutrient intake and nutritional status, characteristics of parents and subject as well as general overview of the location of the study. Chi-square test was used to find out the relationship between nutrient intake and nutritional status.Results: As much as 54.2% of children of Anak Dalam Tribe had varied types of foods and 52.1% of them had good eating frequency; 45.8% had incomplete types of foods and 47.9% had poor eating frequency. Average energy and protein intake of underfives of Anak Dalam Tribe were 1,020.93 ± 298.68 kcal/day and 28.49 ± 8.08 g/day. Most of the children had adequate energy and protein intake (> 80% nutrition sufficiency); i.e. 60.4% and 77.1% subsequently. Those who had inadequate energy and protein intake were 39.6% and 22.9% subsequently. Inadequate nutritional status of underfives of Anak Dalam Tribe using indicator of weight/age was 16.7%, height/age was 12.5%, and weight/height was 8.3%.Conclusion: There was significant relationship between nutrient intake (energy and protein) and nutritional status of underfives of Anak Dalam Tribe.